2021
DOI: 10.1002/ecy.3494
|View full text |Cite
|
Sign up to set email alerts
|

Marginal support for a trophic cascade among sympatric canids in peripheral wolf range

Abstract: Marginal support for a trophic cascade among sympatric canids in peripheral wolf range. Ecology 102(11):e03494.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…This temporal activity pattern better fits the similar result from HMC, where the activity pattern we found would be consistent with the avoidance of wolves. Fowler et al (2021) found little evidence of spatial partitioning between coyotes and wolves in the Upper Peninsula of Michigan (where HMC is located), so temporal partitioning is a plausible coexistence mechanism. The increased nocturnality in the intermediate study areas may be due to the lack of a larger natural predator (the wolf) in combination with higher hunting pressure due to the lower tolerance of rural hunters for coyotes (Drake et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This temporal activity pattern better fits the similar result from HMC, where the activity pattern we found would be consistent with the avoidance of wolves. Fowler et al (2021) found little evidence of spatial partitioning between coyotes and wolves in the Upper Peninsula of Michigan (where HMC is located), so temporal partitioning is a plausible coexistence mechanism. The increased nocturnality in the intermediate study areas may be due to the lack of a larger natural predator (the wolf) in combination with higher hunting pressure due to the lower tolerance of rural hunters for coyotes (Drake et al, 2019).…”
Section: Discussionmentioning
confidence: 99%